ANALISIS KINERJA INSTALASI FARMASI RSU DAERAH X DENGAN PENDEKATAN BALANCED SCORECARD PADA PERSPEKTIF PROSES BISNIS INTERNAL - Indriyati Hadi Sulistyaningrum (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Balanced Scorecard offers the solution for comprehensive performance measurement in a public organization such as a hospital. The purpose of this study is to evaluate the department of pharmacy of RSUD X performance using a balanced scorecard approach refers to internal business perspective. The object of this study is pharmacy department of RSUD X as government district hospitals. This study is a descriptive non-experimental. Data were collected prospectively. The qualitative data obtained through questionnaires and in-depth interviews with the Chief of Pharmacy Department of RSUD X. The quantitative data are dispensing time, drug availability level and interconnection out-patient, obtained through direct observation and surveys on drugs in outpatient prescription. The result showed that the average dispensing times for compounded and non-compounded prescriptions are 21 and 15 minutes respectively. The average of drug availability level in 2012 was 98%. The general interconnection out-patients were at 99%. Therefore, it can be concluded that pharmacy department performance level of RSUD X was categorized in “sufficient criteria”, with some suggestions for improvement. Key words: Performance analysis, balanced scorecard, pharmacy department, RSUD X.